Fluktuasi Harga Bahan Baku Dimasa Pandemi Covid-19 Pada Umkm Mebalfoods - Eka Putri Hana Sabrina; Firdelia Rebecca Qadarisha; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This visit we made was to find out how to deal with rising prices for raw materials in mebalfoods as a whole. The increase in raw material prices during the Covid-19 pandemic has become a big problem for many companies and industries around the world. During the Covid-19 pandemic, rising raw material prices have become a big challenge that must be faced by many companies and industries. This price increase also affected the mebalfoods community, Mebalfoods, which is in the Cikampek sub-district, which was opened by Ms. Mega Triani and her boyfriend Muhammad Iqbal in 2019 and until now it has been going on for 4 years. Increases in prices for basic food ingredients are common in mebalfoods. To overcome the increase in the price of basic food ingredients, the authors provide a solution to increase the selling price to customers. The results of the research on the increase in the price of basic food ingredients greatly affect the selling price of the customer. the research we use is descriptive quantitative, because we conduct survey research to get data that has occurred from the beginning to the present. And from the results of this study we can conclude that the increase in raw material prices needs attention and is the main focus in the government's work agenda.